2017
DOI: 10.1037/pspa0000090
|View full text |Cite
|
Sign up to set email alerts
|

The unique contributions of perceiver and target characteristics in person perception.

Abstract: Models of person perception have long asserted that our impressions of others are guided by characteristics of both the target and perceiver. However, research has not yet quantified to what extent perceivers and targets contribute to different impressions. This quantification is theoretically critical, as it addresses how much an impression arises from "our minds" versus "others' faces." Here, we apply cross-classified random effects models to address this fundamental question in social cognition, using appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
259
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(296 citation statements)
references
References 101 publications
35
259
0
2
Order By: Relevance
“…This pattern is consistent with findings by Hehman, Sutherland, Flake, and Slepian (2017) showing that competence-related judgments depend more on the perceiver's characteristics than on the target's facial features. Noticeably, the ICCs exhibit low values overall, possibly as the result of a guessing response strategy in trials where both target images were equivalent in signal strength (e.g., both high or low in signal).…”
Section: Resultssupporting
confidence: 91%
“…This pattern is consistent with findings by Hehman, Sutherland, Flake, and Slepian (2017) showing that competence-related judgments depend more on the perceiver's characteristics than on the target's facial features. Noticeably, the ICCs exhibit low values overall, possibly as the result of a guessing response strategy in trials where both target images were equivalent in signal strength (e.g., both high or low in signal).…”
Section: Resultssupporting
confidence: 91%
“…Remaining questions in this area are to what extent these findings generalize to other social categories and cultures. Furthermore, we note that estimates indicate that target appearance comprises only 15–25% of the overall variance in impressions (Hehman et al, ; Xie et al, in press), and therefore, there is a ceiling to how much variance target characteristics can explain overall. To fully understand impressions, we have to turn to other sources of variance.…”
Section: Target Contributions To Impressionsmentioning
confidence: 70%
“…Surprisingly, across all dimensions, early evidence suggests that impressions are more driven by perceiver characteristics (~23%) than target characteristics (~15%; Xie et al, in press). This is particularly the case regarding impressions of youthful/attractiveness relative to trustworthiness and dominance dimensions (Germine et al, ; Hehman et al, ; Hönekopp, ; Xie et al, in press).…”
Section: Perceiver Contributions To Impressionsmentioning
confidence: 99%
“…But much research has demonstrated that arrangements of facial features reliably relate to specific trait perceptions [34,35], a process requiring minimal visual exposure [36,37]. Popular models of face-based trait impressions focus exclusively on the role of bottom-up facial features [34,38].…”
Section: Trait Impressionsmentioning
confidence: 99%